From Kutaisi Gimnasium To The Georgian Constituent Assembly - Khositashvili, Mzia (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
In establishing any country as a state, the major role is on politicians, their patriotic approaches and point of view. They create the political-social background of the country. They realize the national ideas. SO, realizing the values which form the public people is important. It’s considered that the 3 societal institutes play a major role in the formation process of a person, these are family, state and school. Family forms personal values, state - general, school - combines personal and societal interests. Sometimes a school has a more important role in terms of person formation that a family. For the 19th century Georgian elite it was a common truth. Managing to retain the national identity for the country, remaining national ideas, issuing the act of independence on May 26, 1918, by the national board are the exploits of the 19th century noble people. Before forming the parliament of Georgia, they elected with direct vote local authority which had to produce governing form and constitution. In the establishing board, there were already people ready for this. According to the statistics given in the article, which is based on the documents kept in the National archives of Georgia, from the members of the establishing board from 130 deputies 63 people had higher education, 11 people had unfinished education, most of them were lawyers, teachers, and journalists. We should remark that the board contained 12 public people. According to the same statistics, most of the deputies were elected from west Georgia, including 36 people from Imereti, 28 of them were graduates of Kutaisi Gimnasium. The article is dedicated to the distinguished graduates of the Kutaisi Gimnasium, who actively participated in the fight for the independence of Georgia, contributed to the work of different committees and commissions of the establishing board, formed the constitution of independent Georgia. They were: Spiridon Kedia, Aleksandre Asatiani, Niko Nikoladze, Grigol Veshapeli, Giorgi Laskhishvili, Simon (Svimon) Mdivani, Ekvtime Takaishvili, Shalva Nutsubidze, SamsonPirtskhalava, Evgeni Gegetchkori, Diomidze Topuridze, Pavle Sakvarelidze, Rajden Arsenidze, Nikoloz Tchkheidze, Irakli Tsereteli, Sergi Japaridze, Konstantine Japaridze, Giorgi Fagava, Grigol Gvelesiani, Ilia Kakabadze, Ivane Zuarabashvili, Simon Avaliani, Ruben Austrovi, Christine Sharashidze, Ioseb Abakelia, Valerian Jugeli, Mikheil Tereteli, Vasil Tsereteli.